Believing as Ourselves: By J Lynn Jones (Beltsville, MD: Amana Publications, 2002. I 60 pages.) (American Journal of Islam and Society, 2003)
This book represents the "female" side of a new genre in Islamic publishing.Jones, a white American convert, educated, well-read, and passionate abouther native tongue and its literature, writes of her experiences as a femaleconvert to Islam and, as the saying goes, ''tells it like it is." Like JeffreyLang, who provides the foreword, the author puts into words the confusion,hurt, bewilderment, and anguish that many converts feel after they comedown from the giddy heights of"saying their shahadah," - experiences thatmay all but extinguish the initial spark of excitement and enthusiasm.The book traces Jones' progress from initial conversion and communityinvolvement, to "burn-out'' and withdrawal, and on to her recoveryfrom depression and marital difficulties. In a pattern familiar to many converts,the initial spiritual delight - even euphoria - is soon swamped bylayer upon layer of community-induced confusion, rebuffs, snubs, dogmatism,and even racism. She speaks with reference to her interaction withthe Arab community, but the pattern will be familiar to many of those whoare either converts to Islam and/or partners in mixed marriages.Jones introduces the Muslim community to the idea of "personalauthenticity" and suggests that converts may suffer greatly when theylose their own ethnic or cultural identity in the effort to become more likethe born-Muslim community in which they find themselves. While this isan interesting idea, a brief search of such terms via my favorite websearch engine led to a host of gay and lesbian sites. Not knowing the pre ciseorigin of the notion of "personal authenticity," it wou Id appear to bea matter that should be handled with caution.The author frankly discusses depression, instead of accepting its beingswept under the carpet and dismissed as "madness" or the product of weakfaith ... and, therefore, one's own fault. This is another area that deserves theMuslim community's further attention, and in which Jones blazes a longoverduetrail. In addition to the spiritual approach, she provides some practicaltools for dealing with it, such as journaling and physical exercise. Thisbrings us back to the issue pertaining to the loss of identity and personalauthenticity, as she asks: How can you come to prayer without your heart?Jones also touches upon women's issues. The chapter on "TheAmerican Harlot," which makes for painful reading, highlights the ...